Measurement of movement patterns to enhance ACL injury prevention - A dead end? - Kam-Ming Mok; Ruen-Shan Leow (Elsevier, 2016)
Vertical drop jump has been suggested to be an effective movement screening task for ACL injury risk, but recent studies have questioned the ability of such tasks to accurately identify players with increased risk of injury. In this paper, we discuss the usefulness of movement screening tests from an injury prevention perspective.